"Quizizz" as An Evaluation of Advanced Natural Science Learning to Increase Concentration in Post-Pandemic Learning - Ekantini, Anita; Damayanti, Ika (Jurnal Inovasi Pendidikan IPA, 2023)
Switching online learning to learning face-to-face (FTF) post-Covid-19 pandemic in the Advanced Natural Science learning course needs good adaptation from the lecturer and student. Students are not yet fully ready to follow learning FTF. When they follow learning, students are not yet entirely focused on learning. This show that the learning concentration of students is low. This research was conducted to evaluate Advanced Natural Science learning post-Covid-19 pandemic. This study aims to determine whether giving quizzes with the application Quiziz affects students' learning concentration. This study uses a quantitative approach with a quasi-experimental method of research. This research design used the pretest-posttest group design. The sample from this study is 36 students 4th Semester Class A 2021/2022 academic year of Education for Islamic Elementary School Teachers (EIEST) with a random cluster sampling technique. The data were analyzed using the t-paired test. From the study, the Quizizz can be made for evaluation on Advanced Natural Science at learning FTF post-pandemic. Students in Advanced Natural Science courses could overcome the lack of concentration by giving quizzes using Quizizz. Besides increasing the learning concentration of students, giving quizzes with the application Quizizz also have several positive impacts. The effects were increased motivation to learn, improved spirit competition, and enhanced understanding of the material.